A INFLUÊNCIA DO PADRÃO ESQUELÉTICO SAGITAL NA DETERMINAÇÃO DO PADRÃO ESQUELÉTICO VERTICAL DA FACE - Brando, Tiago Monteiro (2011)
The goal of this retrospective cephalometric study was to evaluate the influence of the sagittal skeletal pattern to determine the facial type (vertical skeletal pattern of the face) in patients with different malocclusions, who came to UMESP for orthodontic treatment over the past 10 years. For this, we selected initial radiographs of 59 patients who were in average 16 years and seven months old (range: 11 to 25 years). These patients were selected after a subjective analysis of 1600 cases, and grouped as follows: Group 1 Facial Pattern I; Group 2 Facial Pattern II; and Group 3 Facial Pattern III. Following this division, we tested the hypothesis that the determination of facial type differs between two angular measures: SN.GoGn and SN.Gn. To test this hypothesis, we used a logistic regression with errors distributed according to a binomial distribution. Our results show that the probability of congruence between the patterns Gn and SN.GoGn was relatively high (70%) for Pattern I, but for Pattern II (46%) and III (37%) this congruence was relatively low. Apparently, the sagittal skeletal facial pattern (Facial Patterns I, II and III) influenced the determination of facial type. Hence, the use of SN.Gn appears inappropriate to determine the vertical facial skeletal pattern, because Gn. may shift depending on facial patterns.